2021
DOI: 10.3138/canlivj-2020-0024
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmune post-infantile giant cell hepatitis: a case report and review of the literature

Abstract: Giant cell hepatitis (GCH) is a rare entity in adults that is characterized by large multinucleated hepatocyte formation and parenchymal inflammation. We present a case of acute liver failure in a 33-year-old woman secondary to autoimmune hepatitis (AIH). A liver biopsy revealed submassive hepatocyte necrosis consistent with GCH. We conducted a literature review of 187 reported cases of post-infantile GCH in adults. AIH was the most commonly reported cause of GCH, but GCH was associated with a wide spectrum of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…10,13 Also consistent with previous reports, we confirmed that autoimmune liver disease, especially AIH, was the most common etiology associated with PIGCH, accounting for 40% of cases. 1,3,14 Among the 5 PIGCH cases associated with medication, both methamphetamine and Bactrim (trimethoprimsulfamethoxazole) had known liver toxicity; methamphetamine has been previously reported to induce giant cell transformation in hepatocyte. 15,16 .…”
Section: Discussionmentioning
confidence: 99%
“…10,13 Also consistent with previous reports, we confirmed that autoimmune liver disease, especially AIH, was the most common etiology associated with PIGCH, accounting for 40% of cases. 1,3,14 Among the 5 PIGCH cases associated with medication, both methamphetamine and Bactrim (trimethoprimsulfamethoxazole) had known liver toxicity; methamphetamine has been previously reported to induce giant cell transformation in hepatocyte. 15,16 .…”
Section: Discussionmentioning
confidence: 99%
“…Idiopathic cases, in particular, represent only 25%–30% of 200 reported cases. 1 , 2 GCH is defined by giant, multinucleated cells believed to arise from an abnormal hepatocyte response to various stimuli. Pathophysiology remains poorly understood, although a multitude of medications, viruses, autoimmune conditions, and malignancies have been implicated.…”
Section: Introductionmentioning
confidence: 99%